2017
DOI: 10.1242/jcs.188763
|View full text |Cite
|
Sign up to set email alerts
|

Tex19 paralogs are new members of the piRNA pathway controlling retrotransposon suppression

Abstract: Tex19 genes are mammalian specific and duplicated to give Tex19.1 and Tex19.2 in some species, such as the mouse and rat. It has been demonstrated that mutant Tex19.1 males display a variable degree of infertility whereas they all upregulate MMERVK10C transposons in their germ line. In order to study the function of both paralogs in the mouse, we generated and studied Tex19 double knockout (Tex19DKO) mutant mice. Adult Tex19DKO males exhibited a fully penetrant phenotype, similar to the most severe phenotype o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Nonetheless, this was not reflected in higher levels of liver adropin, the protein encoded by Enho. It has been reported that Enho expression in liver results in increased circulating adropin 37 and it may be that the elevated Enho expression in the liver may produce increased adropin secretion while liver adropin levels remain stable (Fig. 4C ).…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, this was not reflected in higher levels of liver adropin, the protein encoded by Enho. It has been reported that Enho expression in liver results in increased circulating adropin 37 and it may be that the elevated Enho expression in the liver may produce increased adropin secretion while liver adropin levels remain stable (Fig. 4C ).…”
Section: Discussionmentioning
confidence: 91%
“…Recent data has suggested that TEX19.1 physically interacts with components of the PIWI-piRNA pathway (Tarabay et al, 2017), although it is not clear whether these proposed interactions have functional consequences for retrotransposon suppression in vivo . Activation of post-translational genome-defence mechanisms may allow mammalian germ cells to safely transcribe retrotransposons by preventing these transcripts from generating RNPs that can mutate the germline genome (Figure 8—figure supplement 1).…”
Section: Discussionmentioning
confidence: 99%
“…In testes, Tex19.1 represses MMERVK10C retrotransposons transcriptionally ( Öllinger et al, 2008 ; Yang et al, 2010 ; Crichton et al, 2017 ), loss of Tex19.1 de-represses multiple retrotransposon RNAs in placenta ( Reichmann et al, 2013 ; Tarabay et al, 2013 ), and TEX19.1/TEX19 proteins interact with UBR2 to promote degradation of LINE-1 retrotransposon proteins in multiple cell types ( Yang et al, 2010 ; MacLennan et al, 2017 ). TEX19.1 has also been reported to interact with components of the piRNA pathway present in testes ( Tarabay et al, 2017 ). We show in this study that both mouse Tex19.1 and human TEX19 inhibit degradation of some N-end rule substrates and regulate AcSMC3-containing cohesin.…”
Section: Discussionmentioning
confidence: 99%
“…Tex19.2 is expressed in somatic cells in the testis and at more restricted stages of gametogenesis ( Kuntz et al, 2008 ; Celebi et al, 2012 ; Hackett et al, 2012 ). Loss of Tex19.2 is reported to not have any major phenotypic consequence in mice, even in a Tex19.1 −/− background ( Tarabay et al, 2017 ). In contrast, loss of Tex19.1 causes fertility defects in both male and female mice ( Öllinger et al, 2008 ; Yang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%